2014
DOI: 10.1126/scitranslmed.3008970
|View full text |Cite
|
Sign up to set email alerts
|

EGFR as a potential therapeutic target for a subset of muscle-invasive bladder cancers presenting a basal-like phenotype

Abstract: Muscle-invasive bladder carcinoma (MIBC) constitutes a heterogeneous group of tumors with a poor outcome. Molecular stratification of MIBC may identify clinically relevant tumor subgroups and help to provide effective targeted therapies. From seven series of large-scale transcriptomic data (383 tumors), we identified an MIBC subgroup accounting for 23.5% of MIBC, associated with shorter survival and displaying a basal-like phenotype, as shown by the expression of epithelial basal cell markers. Basal-like tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
324
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(351 citation statements)
references
References 39 publications
21
324
1
5
Order By: Relevance
“…In agreement with this idea, CCNB1 and CCNE2, whose actions are CDKN2A-independent, are both overexpressed in basal-like bladder tumors presenting an activation of EGFR target genes (48). Mutual exclusivity of FGFR3 and TP53 mutations has been reported for all tumors rather than tumors separated by stage (19).…”
Section: Data Interpretation Using the Modelsupporting
confidence: 56%
See 1 more Smart Citation
“…In agreement with this idea, CCNB1 and CCNE2, whose actions are CDKN2A-independent, are both overexpressed in basal-like bladder tumors presenting an activation of EGFR target genes (48). Mutual exclusivity of FGFR3 and TP53 mutations has been reported for all tumors rather than tumors separated by stage (19).…”
Section: Data Interpretation Using the Modelsupporting
confidence: 56%
“…In the CIT dataset, EGFR-amplified tumors (which belong to the basal-like bladder tumor subtype; ref. 48) do not seem to lose CDKN2A more frequently than FGFR3-mutated tumors, and, more surprisingly, CDKN2A expression is increased when compared with the nonbasal tumors. This suggests two things: (i) CDKN2A may compensate transcriptionally for the loss of RB activation in these tumors; and (ii) in bladder, FGFR3 activates the cell cycle through CDK4/6 (CDKN2A-dependent), whereas EGFR activates the cell cycle in a CDKN2A-independent NOTE: þþ, increase higher than 10% (in absence of DNA damage); þ, an increase higher than 5%; ÀÀ, decrease higher than 10% (in absence of DNA damage); À, a decrease higher than 5%.…”
Section: Data Interpretation Using the Modelmentioning
confidence: 94%
“…Activation of the EGFR pathway has been identified in basal-type MIBC and it was shown that cell lines with this signature were sensitive to EGFR inhibition 198 .…”
Section: Beyond the 'Two Pathway' Modelmentioning
confidence: 99%
“…In addition, a subgroup of muscle-invasive bladder carcinoma displaying a basal-like phenotype is sensitive to EGFR inhibitor erlotinib (5). However, the underlying mechanisms remained unknown.…”
Section: Introductionmentioning
confidence: 99%